2017
DOI: 10.21873/cgp.20028
|View full text |Cite
|
Sign up to set email alerts
|

Mining Exosomal Genes for Pancreatic Cancer Targets

Abstract: Abstract. Background: Exosomes, cell-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Secreted proteins are involved in a variety of physiological processes like immune response, blood coagulation, digestion, cell signaling and cell communication, and include hormones, proteases and digestive enzymes, immunoregulatory cytokines/chemokines and growth factors 17. Non-protein compounds, such as DNAs, RNAs, and lipids, as well as proteins, can be exported by exosomes 1, 18, 19 and mediate important intercellular signaling pathways 20, which may influence local and even distant microenvironments 21.…”
Section: The Secretomementioning
confidence: 99%
“…Secreted proteins are involved in a variety of physiological processes like immune response, blood coagulation, digestion, cell signaling and cell communication, and include hormones, proteases and digestive enzymes, immunoregulatory cytokines/chemokines and growth factors 17. Non-protein compounds, such as DNAs, RNAs, and lipids, as well as proteins, can be exported by exosomes 1, 18, 19 and mediate important intercellular signaling pathways 20, which may influence local and even distant microenvironments 21.…”
Section: The Secretomementioning
confidence: 99%
“…aberrant methylation of CDH1) and alterations in DNA-repair genes (i.e., inactivating mutations of MLH1) are also common (42), while a recent study, using a mouse model of PDAC, identified the transcription factor, RUNX3, as an inducer of metastasis in PDAC (43). Despite this, biomarkers of PDAC remain elusive, although in a recent study, exosomes, extracellular vesicles believed to play a crucial role in pancreatic cancer progression and chemoresistance (44), were found to represent a potentially important resource for identifying therapeutic targets and tools for treating pancreatic cancer (45).…”
Section: Discussionmentioning
confidence: 99%
“…As a screening process, EV testing can allow for the detection of a cancer prior to presentation. This offers the opportunity for earlier diagnosis and better prognosis for patients which have highly lethal and late presenting cancers, such as pancreatic cancer [91] and NSCLC [92]. It is through examination of EV marker proteins and tumour specific marker proteins across different cancer tissues, that the merits of EV study for disease diagnosis become evident [18].…”
Section: Diagnostic Uses Of Evsmentioning
confidence: 99%
“…Considering the presence of specific EV miRNAs and lncRNAs, a panel of pancreatic cancer specific EV biomarkers could potentially be developed for diagnostic purposes. Also, it can display in which biological samples there are the highest numbers of EV transcripts, which could help direct potential diagnostic avenues to be investigated in the future [91].…”
Section: Diagram Showing Examples Of Ev Sites Of Action In the Humamentioning
confidence: 99%